Food Price Spikes, Price Insulation, and Poverty - Anderson, Kym; Ivanic, Maros; Martin, Will (World Bank, Washington, DC, 2013)
This paper has two purposes. It first considers the impact on world food prices of the changes in restrictions on trade in staple foods during the 2008 world food price crisis. Those changes -- reductions in import protection or increases in export restraints -- were meant to partially insulate domestic markets from the spike in international prices. The authors find that this insulation added substantially to the spike in international prices for rice, wheat, maize, and oilseeds. As a result, although domestic prices rose less than they would have without insulation in some developing countries, in many other countries they rose more than they would have in the absence of such insulation. The paper's second purpose it to estimate the combined impact of such insulating behavior on poverty in various developing countries and globally. The analysis finds that the actual poverty-reducing impact of insulation is much less than its apparent impact, and that its net effect was to increase global poverty in 2008 by 8 million people, although this increase was not significantly different from zero. Since there are domestic policy instruments, such as conditional cash transfers, that could now provide social protection for the poor far more efficiently and equitably than variations in border restrictions, the authors suggest it is time to seek a multilateral agreement to desist from changing restrictions on trade when international food prices spike.